2017
DOI: 10.1242/dev.143792
|View full text |Cite
|
Sign up to set email alerts
|

Shh promotes direct interactions between epidermal cells and osteoblast progenitors to shape regenerated zebrafish bone

Abstract: Zebrafish innately regenerate amputated fins by mechanisms that expand and precisely position injury-induced progenitor cells to re-form tissue of the original size and pattern. For example, cell signaling networks direct osteoblast progenitors (pObs) to rebuild thin cylindrical bony rays with a stereotypical branched morphology. Hedgehog/ Smoothened (Hh/Smo) signaling has been variably proposed to stimulate overall fin regenerative outgrowth or promote ray branching. Using a photoconvertible patched2 reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 60 publications
8
82
2
Order By: Relevance
“…Although we have used an inhibitor with off‐target effects on cell proliferation (Armstrong et al. ), our results also support a regulation of initial inter‐ray widening by this pathway, as they agree with narrow inter‐ray phenotypes observed after laser ablation of shh ‐expressing (co‐expressing fgfr1 , Lee et al. ) cells (Zhang et al.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although we have used an inhibitor with off‐target effects on cell proliferation (Armstrong et al. ), our results also support a regulation of initial inter‐ray widening by this pathway, as they agree with narrow inter‐ray phenotypes observed after laser ablation of shh ‐expressing (co‐expressing fgfr1 , Lee et al. ) cells (Zhang et al.…”
Section: Discussionsupporting
confidence: 89%
“…Growth arrest is an off‐target effect of this inhibitor (Armstrong et al. ), precluding any conclusion on SHH/IHH regulation. Nevertheless, these results suggest independent regulation of rays and inter‐rays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the MO-injected regenerates were shorter than the controls, we examined Laminin pattern in 2 dpa noninjected regenerates which have a similar size as the 3 dpa MO-injected regenerate ( Figure 6C). 35 We observed that shha expression was not affected by mmp13a knockdown ( Figure 6E). Therefore, the defect in mmp13a MO-injected regenerates was not due to a delay in Laminin processing/distribution.…”
Section: Knockdown Of Mmp13a Impairs Laminin Organization During Rementioning
confidence: 85%